THE ROLE OF METFORMIN IN THE TREATMENT OF NON-SMALL CELL LUNG CANCER - Ljubicic, Jelena; Pesic, Andrej; Pavlovic, Kasja; Misirlic Dencic, Sonja; Isakovic, Andjelka (HEALTH CARE, 2022)
Out of the all newly diagnosed lung cancers, non-small cell lung carcinoma (NSCLC) comprises 80-85%. When treating advanced stages of the disease, conventional therapy shows poor results, which implies that there is a need for new drugs that will improve the response to current therapy. Metformin, drug used to threat Diabetes mellitus showed promising results in preclinical and retrospective clinical studies. We have analyzed prospective clinical trials investigating the combined effect of conventional therapy and metformin in treating lung cancer, as well as preclinical studies investigating its possible mechanisms of action published in PubMed database in the last 10 years. Several studies indicated that combination therapy with metformin led to the improvement in categories like overal survival and progression-free survival (PFS). However, the number of studies is limited and is characterized by a low number of subjects, as well as by a reduced compliance in subjects using metformin. Preclinical studies suggest cytotoxic effects of metformin, activation of apoptosis, as well as synergistic effect with chemotherapeutics, radiotherapy and biological agents used. The relevance of determined results is questionable, taking into account high metformin concentrations used in vitro. Based on the clinical studies published in the last ten years, there is insufficient data to conclude whether metformin improves prognostic factors in comparison to the conventional therapy. It is also not clear which mechanisms are responsible for possible beneficial effects of metformin. Future preclinical studies thus have to be better designed in order to increase their translational potential, while clinical studies have to be better controlled with improved selection and higher number of subjects enrolled.